Redesain Pasar Umum Tabanan, Kecamatan Tabanan, Kabupaten Tabanan, Bali - Putu Lina Prawisti; Agus Kurniawan; I Nyoman Gede Mahaputra (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
Tabanan Public Market is the largest people's market in Tabanan and is the main choice in terms of shopping for the community, however, referring to the regulation of the Minister of Trade of the Republic of Indonesia concerning the People's Market, there are several problems in the Tabanan Public Market including; [1] lack of supporting facilities and infrastructure in accordance with the standards of the minister of trade of the republic of Indonesia which should have a management office, toilets, re-measurement posts, security posts, breastfeeding rooms, health rooms, worship rooms, fire extinguishing facilities and access, parking lots, places temporary garbage collection, waste treatment facilities, clean water facilities and electricity installations, however, in Tabanan Public Market there are no supporting facilities and infrastructure in the form of re-measurement posts, breastfeeding rooms, health rooms, waste water treatment facilities and clean water facilities. [2] There should be 5 zones in the market zoning, namely the wet food zone, dry food zone, ready-to-eat zone, non-food zone, and poultry slaughter zone, while the Tabanan public market does not yet have these zones.[3] The light intensity test at the Tabanan public market found the amount of lighting did not touch 100 lux, while the health regulations stated a minimum of 100-200 lux.[4] Drainage channels must meet the requirements to be covered with a grid so that the channel is easy to clean, while at the Tabanan Public Market the drainage channel is only partially covered with a grill or grid. From the above problems, it is necessary to re-plan the tabanan public market. Using literature study methods, precedent studies, interviews, measurements, observations and surveys in realizing the Tabanan public market in accordance with the standards of the regulations of the Minister of Trade of the Republic of Indonesia and can make users more comfortable